The development of a customer-based (TQM) quality management model at Universitas Halim Sanusi Persatuan Ummat Islam Bandung - Isep Saepulloh; Johar Permana; Danny Meirawan; Nur Aedi (Inovasi Kurikulum, 2025)
Quality assurance in higher education is a crucial and mandatory aspect for any university, including at Universitas Halim Sanusi Persatuan Ummat Islam Bandung. Educational quality assurance will enhance global competitiveness in terms of the university’s overall quality. The purpose of this article is to explain the development of a customer-based (TQM) quality management model at Universitas Halim Sanusi Persatuan Ummat Islam Bandung. The method used is a descriptive qualitative approach with a PPEPP (Determination, Implementation, Evaluation, Control, and Improvement) standard. The results of the study show that the education quality manual was developed through five stages, involving the BPH, Rectorate (comprising the Rector and Vice Rectors 1–3), Senate, Deans, and Heads of Study Programs. Each party has specific responsibilities and has successfully produced the necessary documents and performance indicators. The development of this quality manual takes into account the goals, vision, and mission of the university, which are aligned with Islamic values. This development improved the education standards and learning outcomes at Universitas Halim Sanusi Persatuan Ummat Islam Bandung according to Islamic values.   Abstrak Penjaminan mutu pendidikan tinggi merupakan hal yang sangat penting dan wajib dalam sebuah perguruan tinggi, begitupun di Universitas Halim Sanusi Persatuan Ummat Islam Bandung. Penjaminan mutu pendidikan akan menciptakan daya saing secara global mengenai mutu perguruan tinggi itu sendiri. Tujuan artikel ini adalah menjelaskan pengembangan model manajemen mutu berbasis pelanggan (TQM) di Universitas Halim Sanusi Persatuan Ummat Islam Bandung. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan PPEPP (Penetapan, Pelaksanaan, Evaluasi, Pengendalian dan Peningkatan) standar. Hasil dari penelitian adalah manual mutu pendidikan dikembangkan melalui lima tahapan oleh BPH, Rektorat (Rektor, Warek 1-3), Senat, Dekan dan Kaprodi. Semua pihak mempunyai tugas masing-masing dan berhasil mengeluarkan dokumen dan indikator kerja yang dibutuhkan. Pengembangan manual mutu ini dilakukan dengan memperhatikan tujuan atau visi dan misi universitas yang mengarah pada nilai Islam. Pengembangan manual mutu ini menghasilkan standar pendidikan dan capaian pembelajaran di Universitas Halim Sanusi Persatuan Ummat Islam Bandung menjadi lebih baik sesuai dengan nilai islam. Kata Kunci: manajemen mutu; pendidikan; perguruan tinggi